Decreasing nervous habits during public speaking: A component analysis of awareness training. Issue 1 (21st September 2021) - Ortiz, Stephanie M.; Deshais, Meghan A.; Miltenberger, Raymond G.; Reeve, Kenneth F.
Abstract : Awareness training can produce decreases in nervous habits during public speaking. A systematic replication of Montes et al. (2020) was conducted to evaluate the independent and additive effects of awareness training components (i.e., response description, response detection) on speech disfluencies during public speaking. We extended prior research by evaluating response description alone, delivering the intervention virtually, using novel videos and speech topics during training, and measuring collateral effects on untargeted responses and speech rate. Response description was sufficient at reducing speech disfluencies for 4 of 9 participants. Response detection (video training) was necessary for 2 participants, and the subsequent addition of response detection (in‐vivo training) was necessary for 3 participants. Reductions were maintained during follow‐up and generalization probes for most participants. Collateral effects of awareness training components were idiosyncratic. A post‐hoc analysis revealed that response description, when effective as a stand‐alone intervention, may be more efficient than the full awareness training package.